AFFILIATION OR INNOVATION? A LITERATURE REVIEW ON YOUNG GENERATIONS’ ECONOMIC PREFERENCES IN THE DIGITAL ERA - Awantari, Ni Nengah Dwi; Sari, Ni Made Anintia Trisna (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Digital transformation has influenced the economic behavior of the young generation, particularly through the rise of digital product affiliation programs such as TikTok Affiliate. This study aims to analyze the tendency of young people to prefer affiliation over building independent businesses and to examine its implications for innovation and entrepreneurship. Affiliation programs provide instant income, flexibility, and low financial risk, making them highly attractive to youth. However, this trend raises concerns that the motivation to build independent businesses and pursue innovation may decline, which in the long run can weaken the entrepreneurial ecosystem. While previous studies have examined digital affiliation and entrepreneurship separately, limited research directly compares youth preferences between these two paths. This paper contributes by highlighting how affiliation and entrepreneurship interact and what this means for future innovation. This study applies a literature review method by synthesizing ten peer-reviewed journals published between 2022 and 2025. The journals were purposively selected based on relevance, credibility, and recency. Data were analyzed descriptively and comparatively to identify motivations, perceptions, and potential impacts of affiliation trends. The analysis shows that ease of access, flexibility, and minimal capital strongly drive youth to engage in digital product affiliation. Independent entrepreneurship, on the other hand, is perceived as riskier, requiring more capital and long-term commitment. As a result, affiliation dominates youth economic activities, but with the consequence of reducing entrepreneurial spirit and innovation. Affiliation provides short-term economic opportunities but may weaken long-term innovation if not balanced with entrepreneurship education. Collaboration among educational institutions, digital platforms, and policymakers is needed to ensure that instant income opportunities align with efforts to foster creativity and innovation among the young generation.